2015
DOI: 10.3109/09286586.2015.1008104
|View full text |Cite
|
Sign up to set email alerts
|

Visual Acuity, Quality of Life and Visual Function Outcomes after Cataract Surgery in Bali

Abstract: Cataract surgery in this population markedly improved QOL, despite a trend towards myopic refractive outcomes. These findings raise questions about biometric methodology, intraocular lens power calculations and refractive targets. Postoperative day 1 VA data may be a reasonable proxy of the intermediate-term rate of non-blind eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
1
8
2
Order By: Relevance
“…13 Although, phacoemulsification is the preferred method for cataract surgery worldwide, it is not always available in developing countries. 14 The mSICS is less expensive, less technology dependent and might be faster than phacoemulsification. Ruit et al 7 revealed that manual SICS is faster than phacoemulsification for advanced cataracts cases.…”
Section: Discussionmentioning
confidence: 99%
“…13 Although, phacoemulsification is the preferred method for cataract surgery worldwide, it is not always available in developing countries. 14 The mSICS is less expensive, less technology dependent and might be faster than phacoemulsification. Ruit et al 7 revealed that manual SICS is faster than phacoemulsification for advanced cataracts cases.…”
Section: Discussionmentioning
confidence: 99%
“…Information materials should be prepared and provided to elders and their family members. Although cataract surgery outcomes are excellent in most countries, some settings do have high rates of poor vision outcomes, which contribute to fear of surgery (Farmer, Innes-Wong, Bergman-Hart, Casson, & Crompton, 2015;Shields et al, 2015). Efforts are needed to improve quality.…”
Section: Barriers To Seeking Eye Care Servicesmentioning
confidence: 99%
“…Shields and colleagues 7 and Thavikulwat and colleagues 8 report the outcome of cataract surgery in rural Lao People's Democratic Republic (Lao PDR) and a mobile clinic in Thailand, respectively. Farmer and co-authors 9 report on visual function and quality of life outcomes for cataract surgery cases in Bali. While good quality outcomes were noted in both Thailand and Indonesia, the findings from Lao PDR showed outcomes considerably below WHO outcome guidelines.…”
mentioning
confidence: 99%